Rodent-borne viruses survey in rural settlers from Central Brazil - Fernandes, Jorlan (2018)
Fil: Fernandes, Jorlan. Fundação Oswaldo Cruz-Fiocruz, Instituto Oswaldo Cruz, Laboratório de Hantaviroses e Rickettsioses, Rio de Janeiro, RJ; Brasil.